CREEP BEHAVIOR OF IRAQI GYPSIFEROUS SOIL - Adnan Hassan Afaj, Hanan; Amaar Mohammed, Hadeel (Journal of Engineering and Sustainable Development, 2017)
The work describes a research study the creep behavior of a gypsiferous soil, the soil used throughout this study was taken from location of Tikrit University site in Salah El-Deen City in Iraq. The soil was clayey sand and classified as (SC) according USCS with a gypsum content of (48.92%). The mineralogical and chemical properties of the soils were determined. The Odometer test was used throughout the test programs. A series of double and single oedometer tests for a long period time were performed in this work . The results indicate that the soil is of low compressibility when loaded under drying condition for both 1day and 64 day respectively while high compressibility it can be noticed for wet soil sample under the same loading period. The collapse potential increases with logarithm of time noticed for 200 kPa stress (8.17% at 1day to 16.17% at 64 days) and (12.2% at 1 day to 14.7% at 64 day) for 1600 kPa stress. The results showed that the increases in collapse potential with the increasing applied stress for the samples loading for 1 and 64 day, also it can be observed high decrease in collapse potential (21.2 % to 14.7 %) after 800 kPa stress for 64 day loading sample. Also the results show nonlinear relations between the creep rate and logarithm of time, the creep rate decrease about (4.4% and 2.5 %) from 1day to 64 day for 200 and 1600 kPa stress respectively.